Cognitive Therapy to Enhance Self Efficacy in Asthmatics - Sutanto, Nadia (ANIMA Indonesian Psychological Journal, 2011)
Asthma is a chronic disturbance of the lungs with inflammation and narrowing of the air pipes.An asthmatic attack could be triggered mainly by physical as well as psychological aspects. Thepsychological aspect is much affected by the patients’ self-efficacy. A cognitive distortion couldbe a contribution for a low self-efficacy. This qualitative descriptive study with a positivisticapproach aimed at enhancing self-efficacy by lowering the cognitive distortion through cognitivetherapy. The informants of this study are two early adult patients with early onset asthma duringchildhood and categorized as non-allergic asthma. The mapping the psychological profile of theinformants using EPPS, and TAT. The self-efficacy mapping used a mixed method design throughthe Stanford Chronic Disease Self-Efficacy Scale and an interview was conducted to delve intothe patient’s self-efficacy shaping source and aspects. The psychological unique profile seems tocontribute to the effectiveness difference of the cognitive therapy in enhancing self-efficacy. Asma adalah gangguan menahun pada paru, ditandai peradangan dan penyempitan salurannapas. Dua aspek pencetus serangan gejala asma yang utama adalah aspek fisik dan psikis.Aspek psikis sangat dipengaruhi keyakinan diri penderita. Distorsi kognitif dapat menjadikontributor terbentuknya keyakinan diri (self-efficacy) yang rendah. Penelitian deksriptif kualitatifdengan pendekatan positivistik ini bertujuan meningkatkan self-efficacy dengan menurunkandistorsi kognitif melalui terapi kognitif. Informan pada studi ini adalah dua orang pada tahapdewasa awal, dengan awitan (onset) asma di masa kanak-kanak dan merupakan penderita asmanon-allergic. Pemetaan profil psikologis menggunakan EPPS, dan TAT. Pemetaan self-efficacydengan mixed-method design melalui instrumen Chronic Disease Self-Efficacy Scale-Stanford danwawancara dilakukan sebagai upaya menggali aspek dan sumber pembentuk self-efficacy.Keunuikan profil psikologis tampak memberikan kontribusi pada perbedaan efektifitas terapikognitif dalam meningkatkan self-efficacy.